2013
DOI: 10.13172/2052-7837-1-1-434
|View full text |Cite
|
Sign up to set email alerts
|

Current trends in the management of maxillofacial gunshot injuries: a critical review

Abstract: Introduction Firearm injuries continue to be a major public health problem. Herein, we review and evaluate the current trends in the management of maxillofacial gunshot injuries. Conclusion Ease of reduction and fixation of fractures, easier restoration of occlusion, prevention of contracture and displacement, ability to reduce displaced or avulsed teeth, early mandibular mobilization, less scarring, less anxiety and shorter hospital stay are among the many benefits associated with comprehensive definitive man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…The iliac crest is a suitable choice for nonvascularized graft to restore bony continuity especially in the mandible because of its dimensional similarity to natural mandible and ease of harvest 1120. Our choice of stainless steel–based fixation devices over the titanium-based equivalent is secondary to the high cost of the latter, despite its obvious benefits of greater biocompatibility and malleability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The iliac crest is a suitable choice for nonvascularized graft to restore bony continuity especially in the mandible because of its dimensional similarity to natural mandible and ease of harvest 1120. Our choice of stainless steel–based fixation devices over the titanium-based equivalent is secondary to the high cost of the latter, despite its obvious benefits of greater biocompatibility and malleability.…”
Section: Discussionmentioning
confidence: 99%
“…9 However, due to the resource limitation, it is impracticable to make CT scan mandatory for all cases in our center and thus requests are made only where it would influence treatment (►Fig. 2a-d) Contemporary paradigm suggests that the first major surgery should be performed with the intent to definitively manage all aspects of the injuries within 48 hours 10,11,19,20 (primary treatment). Our experience has shown that wound contamination, secondary infection, and poor clinical status often compromise early reconstruction attempts in our environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation